Peningkatan Kesehatan Masyarakat Melalui Edukasi Gizi Seimbang Dan Pola Hidup Sehat - Imhar Imhar; Aziz Aziz; Asti Aulia; Andin Eka Fadila; Ayub Suhaidi; Bagas Ariyana; Fitra Aulia Raja; Nabila Rezqi Prameswari; Silvia Givti (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Improving public health is essential to achieving a better quality of life. An effective approach is to educate the public about balanced nutrition and healthy lifestyle practices. While a balanced diet ensures that the body receives the necessary nutrients in appropriate amounts, a healthy lifestyle—including regular exercise, sufficient rest, and avoiding harmful habits—is equally important. These practices help strengthen and improve the immune system, leading to overall well-being and happiness. Educational programs play a crucial role in raising awareness and transforming behaviors toward healthier habits. This document discusses the importance of a balanced diet and a healthy lifestyle while providing strategies for implementing educational programs for individuals and communities. Effective collaboration between the government, health institutions, and society is the key to achieving sustainable health improvements.